(untitled) (The Research of Medical Science Review, 2025)
OBJECTIVE: To compare the effect of conventional therapy and low-level light therapy (LLLT) with near-infrared light-emitting diodes (LED-LLLT) for the treatment of dry eye STUDY DESIGN: Quasi-experimental study. PLACE AND DURATION OF THE STUDY: Tertiary Care Hospital Rawalpindi, from July 2023 to Dec 2023. METHODOLOGY: A 1:1 allocation ratio was used to randomly assign 54 patients to either LED-LLLT (n = 27) or conventional therapy (n = 27). For a total of three treatment sessions, the Low-level light therapy group got Low-level light therapy once a week for three weeks. The change in fluorescein corneal staining (FCS) scores served as the primary outcome measure. Changes in the ocular surface disease index (OSDI) score and tear film break-up time (TBUT) were the secondary goals. These were evaluated before the start of treatment and four weeks later. RESULT: There was a marked improvement in primary end point ( FCS ) in LLLT group than in the conventional therapy group. Secondary end points, TBUT, OSDI also showed more improvement in values in LLLT group than in conventional therapy group. CONCLUSION Compared to traditional therapy, the use of LED-LLLT for dry eye treatment seems to be safer and more effective